Epitaxial growth of wafer-scale two-dimensional polytypic ZnS thin films on ZnO substrates. Issue 17 (12th April 2017) - Wang, Lei; Xiong, Kanglin; He, Yangkun; Huang, Xing; Xia, Jing; Li, Xuanze; Gu, Yiyi; Cheng, Huaqiu; Meng, Xiangmin
Abstract : Wafer-scale polytypic two-dimensional ZnS thin films were successfully grown epitaxially on ZnO bulk substrates, for the first time. Large-area free-standing ZnS membranes were obtained through a simple wet etching method. Abstract : In this paper, we report the first successful epitaxial synthesis of flat wafer-scale two-dimensional ZnS thin films on single-crystalline ZnO substrates with high reproducibility, stability, and reliability, despite the large lattice mismatch (approximately 20%) between ZnO and ZnS. The as-grown ZnS was composed of two crystal phases: wurtzite (WZ) and zinc blende (ZB). The epitaxial orientation between the different phases was identified as: [2−1−10] ZnOWZ //[2−1−10] ZnSWZ //[10−1] ZnSZB and (0001) ZnOWZ //(0001) ZnSWZ //(111) ZnSZB . The crystal structure and the strain profile at the interfaces were studied in detail. After a simple etching treatment, exfoliated large-area free-standing ZnS thin films were achieved for the first time. The present product is expected to become valuable to the strategy of growing large-area thin films or heterostructures with a large lattice mismatch.